Hubungan kreativiti dan ilmu pengetahuan - Mohamad Mohsin Mohamad Said,; Nasruddin Yunos, (Universiti Kebangsaan Malaysia, 2006)
Creative Thinking is not done in a vacuum. It depends on and uses a knowledge base. The knowledge base helps us interpret or understand situations or problems confronting us, and it provides specific information and conceptions which we use in adapting, creating, and solving. This paper takes a look at the relationship between knowledge base and creativity